Haiti : Seventh Review Under the Extended Credit Facility, Requests for Waiver of Nonobservance of Performance Criterion, and Modification of Performance Criteria. - International Monetary Fund. Western Hemisphere Dept. (Washington, D.C. : International Monetary Fund, 2014)
This Seventh Review Under the Extended Credit Facility of Haiti focuses on economic activity that continued to advance in FY2013, despite negative weather events early in the fiscal year. The fiscal deficit increased to 6.7 percent of GDP in FY2013 owing to a gasoline price freeze that dented revenues and on transfers to the electricity sector. The evolution of monetary aggregates reflected government policies and some dedollarization, while the banking system remained well capitalized and profitable. The macroeconomic outlook and the conditions for policy implementation are subject to a number of downside risks.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet